EFFECTS OF YOGIC PRACTICES AND AEROBIC EXERCISE ON VO2 MAX AMONG COLLEGE BASKETBALL PLAYERS - Dr.S.Ezhilarasi; Devimeena Sundaram, CSCS; Dr.S . Kamalakanan; Mr.S.Balasundaram (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
To achieve the purpose of this study, the investigator selected Basketball players from affiliated colleges of Annai Theresa Arts and Science College, Chennai, Tamil Nadu. The subjects were chosen randomly, ranging from 20 to 23 years. They were assigned into three groups: one group as a yogic practice group, the second as an aerobic exercises group, and the third as a combined yogic practices and aerobic exercises group. The experimental groups participated in their training programmes for 12 weeks for their routine. The selected subjects measured their VO2 Max by Cooper’s 12-minute run and walk before and after the training period of six weeks. The differences between the initial and final scores of VO2 Max were subjected to using Analysis of Covariance (ANCOVA). The results of this study proved that the experimental group’s significantly increased VO2 Max. The results further revealed that the combined group significantly increased VO2 Max compared to other groups. The results thus prove that the combined group performed better than the Yogi practices and aerobic exercise groups separately.